Therapeutic Efficacy and Macrofilaricidal Activity of Doxycycline for the Treatment of River Blindness - Walker, Martin (Clin Infect Dis, 2015)
Background. Onchocerca volvulus and lymphatic filariae, causing river blindness and elephantiasis, depend on endosymbiotic Wolbachia bacteria for growth, development, fertility, and survival. Clinical trials have shown that doxycycline treatment eliminates Wolbachia, causing long-term sterilization of adult female filariae and effecting potent macrofilaricidal activity. The continual reinfection by drug-naive worms that occurs in these trial settings dilutes observable anti-Wolbachia and antifilarial effects, making it difficult to estimate therapeutic efficacy and compare different doxycycline regimens, evaluated at different times after treatment. Methods. A meta-analytical modeling framework is developed to link all usable data collected from clinical trials measuring the Wolbachia status and viability of individual female adult worms collected at various times after treatment with 4, 5, or 6 weeks of daily 100 or 200 mg oral doxycycline. The framework is used to estimate efficacy parameters that are not directly measurable as trial outcomes. Results. The estimated efficacy of doxycycline (the maximum proportional reduction in the percentage of adult female O. volvulus positive for Wolbachia) is 91%–94% on average, irrespective of the treatment regimen. Efficacy is >95% in the majority of trial participants. The life span of Wolbachia-depleted worms is reduced by 70%–80%, from approximately 10 years to 2–3 years. Conclusions. The efficacy parameters are pertinent to the prospects of using doxycycline on a “test and treat” basis for onchocerciasis control and confirm doxycycline as a potent macrofilaricidal therapy. The modeling approach is more generally relevant to the design and evaluation of clinical trials for antifilarial drugs conducted in endemic settings.